Studi Pendahuluan Sistem Keamanan Parkir Berbasis Opencv Di Kampus Universitas Indo Global Mandiri - Hastha Sunardi; Nazori Suhandi; John Roni Coyanda; Rachmansyah Rachmansyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
Indo Global Indo Global Mandiri University, is one of the universities in Palembang City which has a fairly large parking area, so it is necessary to have a concept of comfort and security for the academic community and also guests in placing their vehicles in the parking area within the IGM University Campus. This study tries to provide an alternative how to build a vehicle parking concept, especially cars, by detecting vehicle plates and who owns it, so that it can be known early on vehicles that enter an unknown parking area, so that it can be known whether guests are or are treated as people who are not clear. the goal. The research model was built using the Python Programming Language with the OpenCV (Open Source Computer Vision) library as an image processor which with a process or several stages can change the car license plate in the form of an image into a string (word), then by connecting it to the vehicle owner's database. In order to detect who owns the car that will park. The results of the preliminary research, by detecting the vehicle plate in the form of a car image, the results obtained that the area code and plate number can be detected, but other images are also detected. The results show that the plate number is detected as BG 1359 UJ, converted to BG' 13:19 Q UJ. There were 2 conversion failures, namely the number 5 was changed to :1 and the small white circle (bolt) was changed to Q.Keywords: Parking, Detection, Vehicle Plate and OpenCV